VORTEX SHEDDINGS ON THE INSTABILITY AT SUBSEA SUSPENDED PIPELINE - Mastanzade, Nijat; Yılmaz, Levent (AMER SOC MECHANICAL ENGINEERS, THREE PARK AVENUE, NEW YORK, NY 10016-5990 USA, 2008)
The underwater suspended pipeline was investigated for the lateral vibration which is applied for the oscillation of the pipeline part for vortex shedding. Firstly it is defined the tension force at the connection legs on the sea bottom. For definition of the dynamical equation it is used the analogy of the Mathieu Equation. For solution it is used Ince-Struut Diagram. As numerical example it was used the pipeline behavior at the project between Turkey and North Cyprus at the East Mediterranean Sea. In this research the theoretical background is compared with the experimental data of Danish Hydraulic Institute. It shows the good agreement.
Keywords: Subsea Pipeline; Dynamic Behavior; Strutt-Ince Diagram; Oscillation; Denizaltı Boru Hattı; Dinamik Davranışı; Strutt-Ince Şeması; Salınım